Analisis Struktur Beton Bertulang Tahan Gempa Untuk Berbagai Variasi Tinggi Bangunan - Frans Okto Simatupang; Ruddy Kurniawan; Sabril Haris (Universitas Batanghari Jambi, 2023)
Indonesia is a country prone to earthquakes because it is located at the confluence of the Pacific and Trans-Asiatic Circum. Padang is included in the 5-6 earthquake area (KDS E & F), which is an area that has the potential for an earthquake accompanied by the possibility of a tsunami., comfortable and safe against the dangers of an earthquake or tsunami. The most influential factor in the planning of high-rise building structures is the strength of the building structure itself, where this factor is closely related to the safety and resilience of the building in holding and accommodating the loads acting on the structure. Instability in the structure is a basic thing that must be avoided and considered for various types of building heights. An unstable structure when subjected to loads causes the structure to experience a greater deformation than a stable structure. One way that can be done to make the structure more stable is to combine the structure with Shear Walls. Shear wall systems can be used to withstand vertical forces such as gravity loads and horizontal/lateral forces such as earthquake and tsunami loads, thereby preventing excessive swaying of the structure. The use of shear walls is also intended so that when an earthquake and tsunami occurs, the lateral forces that affect the structure are not only resisted by the beam and column elements in the structure but are also resisted by the shear wall system. because the placement of the shear walls that are not appropriate causes the shear forces that occur in the columns and beams to be greater. The research object is multi-storey reinforced concrete buildings with variations in height of 5, 7, 10, 15 and 20 floors. Buildings 5, 7 and 10 floors are designed with an open frame system, while buildings with floors 7, 10, 15 and 20 are designed with a double system, namely open portals and shear walls as lateral load resisters. Open portals use a Special Moment Resisting Frame System (SRPMK) design, while shear walls use a Special Structural Wall System (SDSK) design. The calculated structural loads are dead loads, live loads, superimposed dead loads and earthquake loads. Building location in the city of Padang with moderate soil conditions. The strength and stiffness of structures with shear walls are higher than those without shear walls